Encapsulation of Fresh Spirulina Biomass in Alginate Spheres for Yogurt Fortification - Domenico Siclari; Maria Rosaria Panuccio; Rossana Sidari (Microorganisms)
A new spherification of Spirulina (Arthrospira platensis) was developed for its use as a food supplement. The novelty of this study is the incorporation of fresh Spirulina biomass into alginate spheres formulated with 3% sodium alginate and 1.5% calcium lactate and its addition into yogurt. The spheres and the fortified yogurt were stored at 4 °C for 15 days. The viability of Spirulina, either in contact with the yogurt or not, was evaluated both by OD550nm measurements and microscopic observations. Furthermore, the effect of Spirulina spheres on Streptococcus thermophilus and Lactobacillus bulgaricus was evaluated by enumerating them in standard media. Spirulina retained its viability for up to 15 days when stored separately from the yogurt matrix. Spirulina had a stimulating effect on the lactic acid bacteria: after 15 days, L. bulgaricus and S. thermophilus showed a load increase of 2.66% and 1.64%, respectively, compared to the load detected in the unfortified yogurt. Our study has demonstrated the technical feasibility of producing fresh Spirulina spheres, which can be used alone or added to food preparation. Nevertheless, additional investigations—including quantitative assessment of bioactive compounds and comprehensive sensory analysis—are essential to validate the methodology and support its scalability.